Quantification of Fibronectin Adsorption to Silicone-Rubber Cell Culture Substrates. (April 2002) - Cunningham, James J.; Nikolovski, Janeta; Linderman, Jennifer J.; Mooney, David J.
As the role of mechanical force in cellular signaling gained recognition, investigators designed a number of devices to deliver controlled regimens of mechanical force to cultured cells. One type of device uses thin silicone-rubber membranes to support monolayer cell adhesion and to transmit mechanical force in the form of biaxial strain. We have observed that cell attachment and spreading are impaired on these membranes compared to polystyrene, even when both are passively coated with identical amounts of extracellular matrix. The purpose of these studies was to quantify the efficiency and stability of passive matrix adsorption onto commercially available elastic culture substrates. A theoretically saturating density (1 μg/cm 2 ) of fibronectin was added to each well, and the initial efficiency of adsorption to the walls and elastic membranes was found to be 31 ± 2% of the protein added. Strikingly, when the protein adsorbed specifically to the membranes was quantified after seven days, only 10–26 ng/cm 2 fibronectin were present, revealing that most of the adsorption is to the sides of the wells. These results indicate that the adsorption of matrix proteins to silicone-rubber substrates is relatively inefficient and that investigators who use these systems must be aware of this fact and design their experiments accordingly.